PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN BERBASIS E-LEARNING BAGI GURU SMA SRIJAYA NEGARA PALEMBANG - Ida Sriyanti (Universitas Sriwijaya, 2015)
Purpose of activities to be achieved is to increase knowledge, understanding and skills of high school teachers of Srijaya Negara Palembang in understanding and making media-based learning e-learning so as to increase knowledge, facilitate its tasks and can increase motivation and learning outcomes of high school students ofÂ Srijaya Negara Palembang. This objective can be achieved using a model of devotion that Model B (Assistance) and methods of implementation of this method II (Assistance), specifically methods: (1). Training in the form of presentation of training materials on the history of the Internet, the creation of e-learning using e-learning web This event was accompanied by the entire design team, and (2). Assignment to make all forms of teaching materials based e-learning courses that correspond to each. Based on the results of observation during the activities, it appears that activity in case the participants are very good, this can be seen from the number of training activity indicators that appear. As well as the results of a questionnaire given to participants at the end of the activities, 93% of participants are satisfied with this activity. The training has been able to achieve the expected goals, it can be seen from the tasks given to the participants can be resolved. The expected results of the training participants can be used to develop learning media according to field of study that are taught in schools respectively.